An early report of a screening program for colorectal cancer in Guangzhou, China - Fang, Yujing; Xiao, Binyi; Peng, Jianhong; Tian, Huan; Wang, Fulong; Kong, Lingheng; Lin, Shiyong; Li, Jibin; Su, Qiying; Luo, Kunwu; Ye, Meixian; Ou, Qingjian; et al. (Annals of Translational Medicine, 2019)
Background: We launched a screening program for colorectal cancer (CRC) in Yuexiu District, Guangzhou, China, in 2014. Here we aimed to report the early results of the program and evaluate the benefits of a screening questionnaire. Methods: Residents aged between 50 and 74 were eligible for the screening. A questionnaire and two consecutive fecal immunological tests (FITs) were used as primary screening methods. Subjects who were positive for any of the two tests were referred for further examination with colonoscopy. Neoplasms were removed either colonoscopically or by colectomy. Atypical adenoma and CRC were defined as advanced neoplasms. Results: A total of 6,971 residents in Dadong Street, Yuexiu District were screened with a questionnaire, and among them, 5,343 underwent at least one FIT. Four thousand and two hundred eleven (60.4%) were female, and 2,760 (39.6%) were male, with a median age of 62.0 years. Questionnaire and FITs identified 1,219 candidates for further examination with colonoscopy, among whom only 647 (53.1%) comply. As of this writing, 623 colonoscopy results were obtained, among which 270 (43.3%) had positive findings. The adenoma detection rate (ADR) was 43.3% (270/623). The ADR was 43.3% (270/623). Of the 270 patients, 10 (3.07%) had CRC, 81 (30.0%) had advanced adenoma, 178 had low-grade adenoma or other benign polyps, one had carcinoid. Except for three advanced CRC, all neoplasms detected were benign or in an early stage. Conclusions: Our screening program help identified patients with colonic neoplasms at an early stage, precluding them from developing into the malignant disease. The addition of the questionnaire significantly increased the sensitivity of primary screening, while also decreasing the specificity. Long-term results should evaluate the social and economic benefits of this program.